The Role of Corporate Governance Mechanism on Disclosure of Enterprise Risk Management in Indonesian Banking Industry - Wijayanti, Rita; Ariani, Kurnia Rina; Suyatmin, S (Universitas Muhammadiyah Surakarta, 2022)
This research aims to determine the role of the corporate governance mechanism, which includes the board of commissioners, board of directors, audit committee, institutional ownership, and ownership concentration on enterprise risk management (ERM). The population in this study are banking companies listed on the Indonesia Stock Exchange from 2015 to 2019. Using purposive sampling resulted in 28 companies as the final sample during the 5-year observation period. This study uses multiple linear regression analysis techniques. The results showed that the board of directors, audit committee, institutional ownership, and ownership concentration positively and significantly affected ERM. In contrast, the board of commissioners was not proven.